Author response: CSF concentrations of 5-methyltetrahydrofolate in a cohort of young children with autism. (3rd January 2017) - Shoffner, John
Abstract : On behalf of my coauthors, I thank Dr. Barrett for the comment on our article. 1 Dr. Barrett correctly recognizes that one of the central aspects of our study was to investigate whether a relationship of CSF 5-MTHF levels to symptoms in young children with autism exists. As addressed in the article, a major difficulty in diagnosing cerebral folate deficiency using CSF 5-MTHF levels was the lack of reference intervals from a normal population that would allow defining clinical decision limits. 1 To gain insight into the relationship between CSF 5-MTHF levels and clinical decision limits for young children with autism, we assessed CSF 5-MTHF over time and correlated these levels with detailed clinical assessments. The CSF 5-MTHF levels varied significantly and were not associated with any measures of adaptive behavior, cognitive ability, or autism spectrum disorder symptom severity. As discussed in the article, pediatric CSF normative data that consider natural CSF 5-MTHF variability over time are essential to defining reference intervals as well as critical decision limits. 1 In our cohort of young children with autism, a critical decision limit for CSF 5-MTHF levels was not identified. Further research in patients with autism is needed before CSF 5-MTHF levels can be used to justify lumbar puncture to diagnose cerebral folate deficiency or treatment of patients with compounds such as folinic acid or 5-MTHF.